2017
DOI: 10.1117/1.jmi.4.3.031202
|View full text |Cite
|
Sign up to set email alerts
|

Review of the current status of radiation protection in diagnostic radiology in Africa

Abstract: The aim of this paper is to review the available published studies from African countries on patient doses and medical radiation protection and identify strengths, weaknesses, and challenges. Papers on radiation doses to patients published until 2016 pertaining to studies in African countries were reviewed. Radiography, interventional radiology, computed tomography (CT), and mammography modalities were covered. In radiography, the entrance surface air kerma values were below the established diagnostic referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…This also shows that variations of ESD can be associated with the exposure parameters in X-ray machines. The different technology and technological parameters of an X-ray system may be responsible for such modifications of ESD [21,22]. The measurement variation may also be due to the application for each machine with various filtering and HVL thicknesses.…”
Section: Resultsmentioning
confidence: 99%
“…This also shows that variations of ESD can be associated with the exposure parameters in X-ray machines. The different technology and technological parameters of an X-ray system may be responsible for such modifications of ESD [21,22]. The measurement variation may also be due to the application for each machine with various filtering and HVL thicknesses.…”
Section: Resultsmentioning
confidence: 99%
“…Moussa and Kamoun led a study on workers' knowledge of radiation protection at the CHU Mongi Slim in La Marsa in Tunisia. They reported that the wearing of dosimeters was not respected by 70% of the staff due to the non-existence of this work equipment (Muhogora and Rehani, 2017). The absence of an individual dosimeter is a failure due to the absence of a radiation safety authority or control body.…”
Section: Discussionmentioning
confidence: 99%
“…The data was collected by using self-administered questionnaire and document review. The questionnaire was comprised from socio-demographic and economic, personal, occupational, institutional and environmental factors based on ERPA guidelines, ICRP recommendations, and different literatures [ 10 , 15 , 16 , 22 , 24 ] to address all important variables which affect occupational radiation exposure dose. The data of the respondents was collected utilizing a Google form, which is an electronic-based data collection approach.…”
Section: Methodsmentioning
confidence: 99%
“…However, for a variety of reasons, the amount of occupational radiation exposure dosage is higher in developing countries. Perhaps the most important reasons are a lack of skill and experience, a lack of radiation protection education and training, a lack of radiation protective barriers, poor machine quality (the machines are either old, conventional machines or donated used machines), a lack of equipment calibration, and a lack of machine spare parts [ 10 , 11 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%